Seasonal variability of methyl iodide in the Kiel Fjord. Issue 3 (6th March 2014) - Shi, Qiang; Petrick, Gert; Quack, Birgit; Marandino, Christa; Wallace, Douglas
Abstract From October 2008 to November 2010, CH3I concentrations were measured in the Kiel Fjord together with potentially related biogeochemical and physical parameters. A repeating seasonal cycle of CH3I was observed with highest concentrations in summer (ca. 8.3 pmol L−1; June and July) and lowest concentrations in winter (ca. 1.5 pmol L−1; December to February). A strong positive correlation at zero lag between [CH3I] and solar radiation (R2 = 0.93) was observed, whereas correlations with other variables (SST, Chlorophyll a) were weaker, and they lagged CH3I by ca. 1 month. These results appear consistent with the hypothesis that SSR is the primary forcing of CH3I production in surface seawater, possibly through a photochemical pathway. A mass balance of the monthly averaged data was used to infer mean rates of daily net production (Pnet) and losses for CH3I over the year. The sea‐to‐air flux of CH3I in the Kiel Fjord averaged 3.1 nmol m−2 d−1, the mean chemical loss rate was 0.047 pmol L−1 d−1, and Pnet varied systematically from winter to summer (from 0 to 0.6 pmol L−1 d−1). Pnet was correlated at zero lag with SST, SSR, and Chla (R2 = 0.55, 0.67, and 0.73, respectively, p << 0.01). The lagged cross‐correlation analysis indicated that SSR led Pnet by 1 month, whereas the strongest cross correlations with Chla were at lags of 0 to +1 month, and SST lagged Pnet by 1 month. The broad seasonal peak of Pnet makes it difficult to determine the key factor controlling CH3I net production using in situ concentration data alone.